Reaffirming Human Rights in the Qur’ān and Sunnah - Wang Yongbao (Journal of Islamic Civilization and Culture Review, 2026)
This article aims to elaborate on the views of Islamic law on human rights through the deductive methodologies. The overall idea of this article is to take the Islamic worldview as a background and cite relevant contents such as the Qur’ānic verses, the Sunnah  of the Prophet Muḥammad (peace be upon him ) and his Companions (may Allāh’s pleasure on them), as well as to study the topic through understanding contents generated during the development of Islamic jurisprudence (7th-10 century AD.), in order to truly reflect human rights under the justice of Islam, that is, applying the metaphysics and physics of Islamic teachings as the basic theory to construct a harmonious human rights system, where the rights and obligations of multiple religions, races, and cultures can certainly coexist in any society of any state. However, for the theory and practice of human rights, this article not only reflects on the decline of Islamic civilization and the subsequent consequences of the Muslim world being controlled and dominated by various colonial forces, but also conducts self-criticism.Through calfuly and deeply study, it can be concluded that human rights under the Islamic legal system are not only a detailed and wide-ranging framework, but also a network of interconnected and complementary rights and obligations, becase under the Islamic legal system, the emphasis on human rights is seen as an essential component of a complete cosmic system.